A facile approach to enhance the hydrogen evolution reaction of electrodeposited MoS2 in acidic solutions. (29th November 2022) - Liang, Tianyue; Jia, Haowei; Zhou, Yingze; Fan, Jiajun; Xu, Yeqing; Hu, Yifan; Zhou, Lu; Wang, Caiyun; Chen, Fandi; Guan, Peiyuan; Li, Mengyao; Wan, Tao; et al.
Abstract : Binder-free Ni modified-MoS2 electrocatalysts with superior hydrogen evolution reaction (HER) catalytic performance were fabricated by a facile electrodeposition method. Abstract : Molybdenum disulfide (MoS2 ), a typical two-dimensional transition metal dichalcogenide (TMD), has been widely used as an electrocatalyst for the hydrogen evolution reaction (HER). This work presented a facile electrodeposition method to fabricate binder-free Ni modified-MoS2, exhibiting superior HER catalytic performance under acidic conditions. The characterization results revealed that the as-deposited Ni–MoS2 samples have extended interlayer spacings after Ni intercalation into layered structure MoS2 . The as-synthesized MoS2 with 5 at% Ni ion addition exhibits excellent electrocatalytic activity with a low onset overpotential of 139 mV. The Ni0.05 Mo0.95 S2 sample also exhibits the slightest Tafel slope of 62 mV dec −1, suggesting a promoted Volmer-Heyrovsky process. Besides, a low overpotential of 215 mV at 10 mA cm −2 and a high stability in H2 SO4 solutions were also achieved. The excellent HER performance of the obtained material can be attributed to the synergistic effect of the formed Ni–Mo–S composition, abundant active sites and increased electrical conductivity. This work may contribute to the practical application of TMD-based electrocatalysts for hydrogen production.